Selected College Students' Knowledge and Perceptions of Biotechnology Issues Reported in the Mass Media - Gary J. Wingenbach; Tracy A. Rutherford; Deborah W. Dunsford (Journal of Applied Communications, 2002)
The purpose of this study was to determine college students' awareness of and attitudes toward biotechnology issues reported in the mass media. Future agricultural communicators (N = 330) representing 11 land-grant universities in 10 states recorded their knowledge and perceptions of biotechnology issues as reported in the mass media. Respondents were mostly seniors (46%), female (55%), and considered themselves "8" average students (60%). Students achieved only 30% correct responses (M = 3.05) in a knowledge assessment of biotechnology practices, illustrating a lack of knowledge. However, nearly 84% of the respondents perceived their level of knowledge as average to high (24% perceived they possessed above-average scientific knowledge). Future agricultural communicators were somewhat accepting of biotechnology practices for genetically modified organisms involving plant life (M = 3.28), but viewed these same practices as somewhat unacceptable for use on humans (M = 1.84). Significant, low positive relationships existed between respondents' perceived and assessed levels ofbiotechnology knowledge (r = .17) and between their assessed knowledge and acceptance of biotechnology practices (r = .16). Selected college students in the agricultural sciences have much less knowledge about biotechnology practices than what they believed to possess. Although correctable through increased study of biotechnology, this finding may pose serious problems for students choosing to "communicate" the science of biotechnology issues in the mass media. Agricultural communications faculty nationwide should analyze their curricula to determine if students are being given the opportunity to study biotechnology issues while learning how to communicate it to a larger audience.